Optimizing the ultrasonic inserting parameters to achieve maximum pull – Out strength using response surface methodology and genetic algorithm integration technique. (March 2017) - Anand, K.; Elangovan, S.
Highlights: RSM - GA integration technique is proposed for optimizing the ultrasonic insertion process. Experimental design was created based on the central composite designs (CCD). Experiments are conducted by considering three inserting parameters namely pressure, inserting time and holding time. Higher pullout strength can be achieved by adjusting inserting conditions with the help of an RSM - GA integration method. Abstract: This paper aims at developing an effective methodology to find the optimum inserting conditions that maximize the pullout strength of joints produced by ultrasonic insertion process using response surface methodology (RSM) and genetic algorithm (GA). Experiments were planed as per central composite design of experiments. The second order mathematical model for pullout strength was developed using response surface methodology with pressure, inserting time and holding time as process parameters. The developed RSM model is then coupled with GA, to determine the optimal inserting conditions. The results of this study revealed that the proposed RSM – GA integration technique managed to find the optimum inserting conditions, which leads to the maximum value of inserting performance when compared to the RSM results.